Perlindungan Hak Konstitusional Masyarakat Pesisir : Urgensi Harmonisasi Regulasi Pengelolaan Pesisir Terpadu - Mohammad Mahrus Ali; Zaka Firma Aditya; Abdul Basid Fuadi (Jurnal Konstitusi, 2020)
Ten years ago, the Constitutional Court Decision Number 3/PUU-VIII/2010 confirmed that the granting of concession rights for coastal waters (after this: HP3) by the government to private parties was contrary against the constitution, especially Article 33 paragraph (4) of the 1945 Constitution. Legislators then respond to the decision to revise Law No. 27 of 2007 as Law No. 1 of 2014 on the Amendment of Law No. 27 of 2007 on the Management of Coastal Areas and Small Islands. The revision has changed the HP3 regime from Law 27/2007 to the licensing regime in Law 1/2014. Unfortunately, these changes would lead to various juridical problems ranging from conflict between the laws and regulations under legislation that ultimately is potentially detrimental to the constitutional rights of coastal communities. This research focuses on juridical and sociological aspects related to the coastal communities protection of constitutional rights after the Constitutional Court Decision Number 3/PUU-VIII/2010. This research in-depth discusses the follow-up of the Constitutional Court decision a quo by legislators, central government, local governments, stakeholders, and the fulfilment of the constitutional rights of coastal communities. This research is normative legal research by examining the Constitutional Court decision Number 3/PUU-VIII/2010. The descriptive discussion used to understand coastal zone management law's politics to fulfil the constitutional rights of coastal communities. Besides, integrated coastal zone management (Integrated Coastal Zone Management) is a dynamic process, multidisciplinary, and repeated to promote sustainable coastal areas' sustainable management. It includes the whole cycle of information collection, planning, decision-making, management, and implementation monitoring.